Comparative Transcriptome Analysis Revealed Genes Regulated by Histone Acetylation and Genes Related to Sex Hormone Biosynthesis in Phytophthora infestans - Wang, Xiao-Wen; Lv, Jia-Lu; Shi, Ya-Ru; Guo, Li-Yun (Frontiers in Genetics, 2020)
Late blight caused by Phytophthora infestans, is one of the most devastating diseases of potato, and was responsible for the death of millions of people during the Irish Potato Famine in the 19th century. Phytophthora infestans is a heterothallic oomycete that typically requires two compatible types (mating types), A1 and A2, to complete sexual reproduction (i.e., oospore production). Oospores have critical effects on disease epidemiology because they serve as the primary inoculum in subsequent growing seasons. The sexual reproduction of Phytophthora species is regulated by α hormones. In previous studies, we proved that transformants in which selected histone deacetylase (HDAC) genes are silenced exhibit abnormal hormone production. In the current study, we compared the transcriptomes of HDAC-silenced and wild-type strains to explore the genes regulated by HDAC and the genes involved in sex hormone biosynthesis in Phytophthora species. A total of 14,423 transcripts of unigenes were identified in the wild-type strain, the HDAC family-silenced transformant (HDST), and the HDAC7-silenced transformant (H7ST). After comparing the intergroup gene expression levels, 1,612 unigenes were identified as differentially expressed among these strains. The expression levels of 16 differentially expressed genes (DEGs) were validated by quantitative real-time PCR. The functional annotation of the DEGs by gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses indicated that HDACs affect the expression of genes related to metabolic and biosynthetic processes, RNA processing, translation, ribosome biogenesis, cellular structural constituents, RNA binding, and protein binding. Moreover, HDAC7 specifically influences the transcription of genes associated with transport, methylation, mitochondria, organelle inner membranes, receptors and transporters, and hydrolase activities. We also identified 18 candidate genes related to α hormones biosynthesis, including a gene encoding the NF-Y transcription factor (PITG_10861). The overexpression of PITG_10861 increased the production of hormone α2. The results of this study revealed P. infestans genes affected by histone acetylation. The data presented herein provide useful inputs for future research on the epigenetic mechanisms and mating behaviors of Phytophthora species.